Dust, Sand, and Winds Within an Active Martian Storm in Jezero Crater. Issue 17 (9th September 2022) - Lemmon, M. T.; Smith, M. D.; Viudez‐Moreiras, D.; de la Torre‐Juarez, M.; Vicente‐Retortillo, A.; Munguira, A.; Sanchez‐Lavega, A.; Hueso, R.; Martinez, G.; Chide, B.; Sullivan, R.; Toledo, D.; et al.
Abstract: Rovers and landers on Mars have experienced local, regional, and planetary‐scale dust storms. However, in situ documentation of active lifting within storms has remained elusive. Over 5–11 January 2022 (LS 153°–156°), a dust storm passed over the Perseverance rover site. Peak visible optical depth was ∼2, and visibility across the crater was briefly reduced. Pressure amplitudes and temperatures responded to the storm. Winds up to 20 m s −1 rotated around the site before the wind sensor was damaged. The rover imaged 21 dust‐lifting events—gusts and dust devils—in one 25‐min period, and at least three events mobilized sediment near the rover. Rover tracks and drill cuttings were extensively modified, and debris was moved onto the rover deck. Migration of small ripples was seen, but there was no large‐scale change in undisturbed areas. This work presents an overview of observations and initial results from the study of the storm. Plain Language Summary: Mars commonly has local and regional dust storms, some of which grow into global dust storms. Until now, no lander or rover on Mars has observed the meteorology and processes within an active lifting storm center. The Perseverance rover experienced a large regional storm in Jezero crater over six sols (Martian days) in January 2022. It documented active dust lifting and winds reshaping the Martian sediment. Winds increased as the storm approached but were only directly monitored until the afternoon of the first sol, when the wind sensor failed during high winds. Winds, even after the loss of the wind sensor, were powerful enough to blow sand and lift dust around the rover. Rover imaging showed 21 dust devils and other dust lifting events near noon of the first sol. Images of the rover and terrain showed that there were several incidents of sediment mobilization immediately around the rover. Rover tracks were erased or heavily modified, cuttings from a recent drilling were removed, and sediment was deposited across the rover's deck. The changes wrought by the storm were concentrated on areas where the rover had previously modified the terrain, except for sand motion including the migration of small sand ripples. Key Points: The Perseverance rover documented the meteorology and effects of a dust storm as it passed over Jezero crater, Mars The storm brought damaging winds and wide‐spread dust lifting, while modifying the pressure amplitudes and thermal cycle at the site Winds extensively modified previously disturbed areas, while sand motion and small‐scale ripple migration occurred all around the rover